In vitro efficacy of Capparis spinosa L. alcoholic extract in controlling the hairy grain beetle (khapra) Trogoderma granarium Everts (Coleoptera Dermestidae) - Hussain, Farah Hadi Abdul; Rashid, Yousef Dakhil (Indian Journal of Plant Protection, 2023)
The research was carried out to investigate the effects of the alcoholic extract of the leaves and roots of C. spinosa, at concentrations of 10, 20, and 30 mg/ml on the larvae of the second and fourth instars of the hairy grain beetle (Khapra) Trogoderm granarium. The results showed the superiority of the alcoholic extract of the leaves at the concentration of 30 mg/ml in killing the second and fourth larval instars, with mortality rates of 48.3 and 60.0%, respectively. As for the alcoholic extract of the roots, the concentration of 30 mg/ml caused the highest mortality rate in the second and fourth larval instars, with mortality rates of 23.3 and 28.3%, respectively.